PECULIARITIES OF FORMATION OF SALT PLUGS IN OIL AND GAS INDUSTRY HEAT EXCHANGERS - Kurbanov Farkhod Polatovich; Rayimov Zukhriddin Khayriddin ugli; Akhmedov Vohid Nizomovich (American Journals Publishing, 2025)
Heat exchangers are a very important part of technological devices in the chemical industry and related fields. The share of heat exchangers in the oil and gas processing industry is 50%. This article is devoted to the study of the problem of formation of salt plugs in heat exchangers of the oil and gas industry
Keywords: Salt plugs, shell-and-tube heat exchangers, plate heat exchangers, heat transfer, circulating water, salt deposits, carbonate salts, silicate salts.